Challenges and opportunities for online education of veterinary sciences in Kazakhstan - Kadyrov, Ablaikhan; Ussenbayev, Altay; Kurenkeyeva, Dariyash; Abdrakhmanova, Aruzhan; Mukhanbetkaliyev, Yersyn; Adilbekov, Zhanat; Perez, Andres; Abdrakhmanov, Sarsenbay (Frontiers in Computer Science, 2024)
The Severe Acute Respiratory Syndrome Coronavirus Infectious Disease 2019 (SARS-COVID-19) pandemic has dramatically improved the attitude that society has toward educational opportunities that are administered online. In many cases, digital platforms were adapted and utilized without formal evaluation of the needs, constraints, and opportunities associated with their use. Here, the eight historical faculties of veterinary sciences of Kazakhstan were surveyed to gather data on the use of online technology for the discipline in the country and the limitations, opportunities, and challenges associated with its use. Results show that technological resources, institutional support, and faculty and instructors' attitudes are highly favorable for the implementation of online education programs consistently throughout the country. In contrast, students' motivations and skills are perceived as variable, although generally favorable, at different locations. The results here provide insights into the challenges and opportunities associated with using online technology for instruction in veterinary sciences in Kazakhstan, which will help create the foundations for implementing this type of program in the country and region.